Research on the Construction of Virtual Teaching and Research Room based on Audit Course - Liu, Bo; Zhao, Renzheng; Sun, Guoping (International Journal of Global Economics and Management, 2025)
With the rapid development of information technology, traditional audit course teaching is facing many challenges. This article aims to explore the application of virtual teaching and research rooms in the teaching of auditing courses, analyze the difficulties of traditional auditing course teaching, study the advantages of virtual teaching and research rooms, including improving teaching quality, promoting balanced allocation of resources, and achieving integration of industry and education. Specific construction paths are proposed to improve the quality of education and teaching, optimize teachers’ professional abilities, and promote balanced allocation of educational resources.